Spremljanje demence v Sloveniji Epidemiološki in drugi vidiki - Lovrečič, Barbara; Lovrečič, Mercedes (ZRC SAZU, Založba ZRC, 2021)
Every three seconds, a new case of dementia emerges in the world, and by 2050 there will be at least 150 million persons with dementia. The World Health Organization declared dementia for a public health priority of the 21st century before the emergence of the SARS-CoV-2/COVID 19, which affected the elderly population the most. Dementia is a disease that affects the individual, caregivers and wider society. Due to increasing dependence from others, dementia causes a health, economic, emotional, psychological and physical burden for the person with dementia and his caregivers. There is still a great stigma associated with dementia. Less than half of people with dementia are diagnosed and treated, although we have drugs available that can slow the course of the disease. In the multi-author's monograph Monitoring of Dementia in Slovenia: Epidemiological and other aspects, we addressed the problem of dementia, especially in relation to COVID-19. The publication also highlights the estimates on the prevalence of dementia in Slovenia, which were made on Slovenian data and the population of Slovenia. The publication is distinguished by a multidisciplinary treatment of the topics and is intended for both the lay and the professional public.